search points attachment profile arrow left arrow right star heart verified symbols equation arrow-down question mark check menu accountancyadministrationagriculturalalgebraallarabicartart_musicbelarusbelarus_altbiologybusinesscatalachemistrychineseeconomicsegzamenglishentrepreneurshipenvironmentethicseuskarafirst_aidfrenchgalegogeographygeologygeometrygermangrammarhealthhistoryindia_langindonesian_langinformaticsitalianjapanesekazachkazach_altkoreanlanguagelatinlawlife_scienceliteraturelogicmathematicsmusicnigerian_langother_languagesotherspedagogicsphilosophyphysical_educationphysicspoliticspsychologyreligionrpa_langrussianrussian_altsciencesecurityskillssocial_sciencesociologyspanishstatisticstechnologytourismtrafficukrainianukrainian_altukrainian_literaturewos_civilisation accountancyadministrationagriculturalalgebraall_1arabicartart_music_2belarusbelarus_altbiologybusiness_2catalachemistry_1chineseeconomicsexam_3englishentrepreneurshipenvironment_2ethicseuskarasecurity_1frenchgalegogeography_4geology_4geometrygermangrammarhealthhistoryindia-langindonesian-langinformaticsitalianjapanesekazachAsset 230koreanlanguagelatinlawlife-scienceliteraturelogic_2mathematicsmusicnigerian-langotherlanguagesother_1pedagogicsphilosophyphysical_educationphysicspoliticspsychologyreligion_1rpa-langrussianrussian_altsciencesecurity_3_mskills_1allsocial_science_5_msociologyspanishstatisticstechnologytourismtrafficukrainianukrainian_altukrainian_literaturewos_civilisation

Ответ

Проверено экспертом

Ответ дан
drakerton

Ответ:

а) (5-3frac{7}{16}) + (4-2frac{9}{16}) = 1frac{9}{16} + 1frac{7}{16} = 3

б) (3-1frac{4}{7}) + (5-2frac{5}{7}) = 1frac{3}{7} + 2frac{2}{7} = 3frac{5}{7}

в) (2-1frac{5}{9}) + (4-1frac{4}{9}) = frac{4}{9} + 2frac{5}{9} = 3

г) (2-1frac{5}{18}) + (7-2frac{11}{18}) = frac{13}{18} + 4frac{7}{18} = 4frac{20}{18} = 5frac{2}{18} = 5frac{1}{9}

а) (6-3frac{5}{12}) - (3-1frac{1}{12}) = 2frac{7}{12} - 1frac{11}{12} = 1frac{19}{12} - 1frac{11}{12} = frac{8}{12} = frac{2}{3}

б) (5 - 2frac{7}{19}) - (4-3frac{2}{19}) = 2frac{12}{19} - frac{17}{19} = 1frac{31}{19} - frac{17}{19} = 1frac{14}{19}

в) (7-3frac{7}{11})-(4-2frac{3}{11}) = 3frac{4}{11} - 1frac{8}{11} = 2frac{15}{11} - 1frac{8}{11} = 1frac{7}{11}

г) (8-4frac{13}{20}) - (6-5frac{3}{20}) = 3frac{7}{20} - frac{17}{20} = 2frac{27}{20} - frac{17}{20} = 2frac{10}{20} = 2frac{1}{2}

Удачи!

Ответы и объяснения

Не тот ответ, который тебе нужен?